The Preliminary Study on Klungsu (Tamarind Seed) as An Alternative Material for Dental Calculus Remover - Ratnawati Hendari; Sulur Joyo Sukendro; Sadimin Sadimin (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
This study was aimed at knowing the availability of Klungsu (Tamarind seed) as remover and cleaner for dental calculus. The study followed Completely Randomized Design with three treatments and tested with Ftest and Duncan Multiple Range Test. The availability was studied by soaking the calculus and enamel at two concentrations (0 and 25%) of Klungsu and one group without soaking (dry group). The results showed that soaking in Klungsu solution significantly decreased (p<0.05) the strength of dental calculus, but no significantly differences (p>0.05) were found for enamel. The conclusion could be drawn from this study was klungsu could be used as an alternative cleaning material for removing dental calculus and safe for dental enamel.